2018
DOI: 10.1038/s41390-018-0170-1
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to perfluoroalkyl substances and adipocytokines: the HOME Study

Abstract: Despite known associations with reduced birthweight, gestational serum perfluoroalkyl substances concentrations were not associated with neonatal adipocytokine concentrations. Further exploration of pathways of perfluoroalkyl substances associated changes in birthweight may help identify biomarkers that could be used to identify at-risk populations and develop interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Although some animal experiments [83] and observations in humans [84,85] found negative associations between PFAS and Leptin concentrations, often positive associations were observed. Experimental evidence for induction of higher leptin concentrations by PFAS was observed in human cells in vitro [86] and in animals [87][88][89][90] and also observations on humans showed positive associations between internal exposure to PFAS and leptin serum concentrations [91][92][93]. Specially relevant in relation to our findings concerning cognition in elderly people is the observation of Ding et al [94] who found that, in women aged 45-56, higher PFAS concentrations were associated with higher leptin and free leptin values.…”
Section: Difference In Impact Between Adolescents and Older Adultssupporting
confidence: 52%
“…Although some animal experiments [83] and observations in humans [84,85] found negative associations between PFAS and Leptin concentrations, often positive associations were observed. Experimental evidence for induction of higher leptin concentrations by PFAS was observed in human cells in vitro [86] and in animals [87][88][89][90] and also observations on humans showed positive associations between internal exposure to PFAS and leptin serum concentrations [91][92][93]. Specially relevant in relation to our findings concerning cognition in elderly people is the observation of Ding et al [94] who found that, in women aged 45-56, higher PFAS concentrations were associated with higher leptin and free leptin values.…”
Section: Difference In Impact Between Adolescents and Older Adultssupporting
confidence: 52%
“…Previous studies on adipokine hormones at birth primarily focused on leptin and adiponectin, and somewhat mixed results have been reported. In the HOME study of 230 mother-infant pairs, no associations were seen between the 2nd trimester serum-PFAS concentrations (i.e., PFOA, PFOS, PFHxS, and PFNA) and cord blood leptin and adiponectin ( Buck et al, 2018 ). When stratifying by sex, PFNA was associated with increased leptin in males but decreased leptin in females.…”
Section: Discussionmentioning
confidence: 96%
“…Potential confounders were selected and included in the regression model if they had been associated with prenatal and childhood PFAS concentrations and metabolic functions in prior literature (directed acyclic graphs are included as Figure S1 and S2 ) ( Braun et al, 2016 ; Buck et al, 2018 ; Domazet et al, 2020 ; Fleisch et al, 2017 ; Halldorsson et al, 2012 ; Hoyer et al, 2015 ; Karlsen et al, 2017 ; Mora et al, 2017 ; Shelly et al, 2019 ). We included maternal education and child sex in all models.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 , 12 These hormonal factors include leptin and its receptor, adiponectin, and resistin, which are associated with childhood growth and with the odds of being or becoming overweight and developing chronic disease. 12 14 Serum-adipokine concentrations may be affected by other factors, e.g., preterm birth that appears to be associated with lower adiponectin and higher leptin and resistin in later childhood. 14 , 15 In addition, the duration of breastfeeding may be of potential importance, as the presence of adipokines has been detected in human milk.…”
Section: Introductionmentioning
confidence: 99%